Bell's Palsy in Children (BellPIC): protocol for a multicentre, placebo-controlled randomized trial. Issue 1 (December 2017) - Babl, Franz; Mackay, Mark; Borland, Meredith; Herd, David; Kochar, Amit; Hort, Jason; Rao, Arjun; Cheek, John; Furyk, Jeremy; Barrow, Lisa; George, Shane; Zhang, Michael; et al.
Abstract Background Bell's palsy or acute idiopathic lower motor neurone facial paralysis is characterized by sudden onset paralysis or weakness of the muscles to one side of the face controlled by the facial nerve. While there is high level evidence in adults demonstrating an improvement in the rate of complete recovery of facial nerve function when treated with steroids compared with placebo, similar high level studies on the use of steroids in Bell's palsy in children are not available. The aim of this study is to assess the utility of steroids in Bell's palsy in children in a randomised placebo-controlled trial. Methods/Design We are conducting a randomised, triple-blinded, placebo controlled trial of the use of prednisolone to improve recovery from Bell's palsy at 1 month. Study sites are 10 hospitals within the Australian and New Zealand PREDICT (Paediatric Research in Emergency Departments International Collaborative) research network. 540 participants will be enrolled. To be eligible patients need to be aged 6 months to < 18 years and present within 72 hours of onset of clinician diagnosed Bell's palsy to one of the participating hospital emergency departments. Patients will be excluded in case of current use of or contraindications to steroids or if there is an alternative diagnosis. Participants will receive either prednisolone 1 mg/kg/day to a maximum of 50 mg/day or taste matched placebo for 10 days. The primary outcome is complete recovery by House-Brackmann scale at 1 month. Secondary outcomes include assessment of recovery using the Sunnybrook scale, the emotional and functional wellbeing of the participants using the Pediatric Quality of Life Inventory and Child Health Utility 9D Scale, pain using Faces Pain Scale Revised or visual analogue scales, synkinesis using a synkinesis assessment questionnaire and health utilisation costs at 1, 3 and 6 months. Participants will be tracked to 12 months if not recovered earlier. Data analysis will be by intention to treat with primary outcome presented as differences in proportions and an odds ratio adjusted for site and age. Discussion This large multicenter randomised trial will allow the definitive assessment of the efficacy of prednisolone compared with placebo in the treatment of Bell's palsy in children. Trial registration The study is registered with the Australian New Zealand Clinical Trials RegistryACTRN12615000563561 (1 June 2015).